2007
DOI: 10.4103/0250-474x.39435
|View full text |Cite
|
Sign up to set email alerts
|

Haematinic evaluation of <i> Lauha bhasma</i> and <i> Mandura bhasma</i> on HgCl<sub> 2</sub> -induced anemia in rats

Abstract: New Antihistaminic Agents: Synthesis and Evaluation of H1-Antihistaminic actions of 3-[(N,N-Dialkylamino)alkyl)-1,2,3,4-tetrahydro-(1H)-thioquinazolin-4(3H)-ones and Their oxo Analogues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…[26272829303132333435363738] Amalaki , due to Madhura Rasa (sweet taste) and Sheeta Virya (cold potency) reduces Pitta [2627] and thus breaks down the main factor in the pathogenesis of Pandu Roga . Further, it contains richest source of vitamin-C, which helps in the absorption of iron thus increases its bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26272829303132333435363738] Amalaki , due to Madhura Rasa (sweet taste) and Sheeta Virya (cold potency) reduces Pitta [2627] and thus breaks down the main factor in the pathogenesis of Pandu Roga . Further, it contains richest source of vitamin-C, which helps in the absorption of iron thus increases its bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…[3031] Lauha Bhasma , the oxide of iron has a direct impact on bodily iron. [32333435363738] Thus, the double fold increase in the Pitta aggravation (due to fertile age and Dauhrid ) in pregnancy, Dhatrilauha possesses many fold effectiveness in anemia (IDA). This is evidenced with the significant results obtained in the majority of parameters in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauha bhasma possesses significant hematinic and cytoprotective activity. 12 Lauha bhasma also has hemoglobin regeneration efficacy. As per Ayurveda, Triphala is antianemic and antioxidant.…”
Section: Probable Mode Of Action Of Therapymentioning
confidence: 99%
“…Lauha (iron) preparations are said to be effective in IDA. 12,13 Based on Ayurveda classics and previous studies conducted on IDA, Lauha preparations, such as Navayasa Churna are observed to be effective in IDA, due to its Pandughna (antianemic), Prinana (nourishing and replenishing), and Raktaprasadana (providing qualitative and quantitative excellence) properties. Traditionally, Navayasa Churna is successfully used by Ayurvedic physicians for the management of Pandu.…”
Section: Introductionmentioning
confidence: 99%